2017
DOI: 10.1002/ejic.201601396
|View full text |Cite
|
Sign up to set email alerts
|

Improved (Photo)catalytic Propene Hydration in a Gas/Solid System by Using Heteropolyacid/Oxide Composites: Electron Paramagnetic Resonance, Acidity, and Role of Water

Abstract: Binary materials composed of the oxides SiO 2 , TiO 2 and N-doped TiO 2 and the Keggin heteropolyacid (PW 12 ) were prepared and physicochemically characterized. They were used as catalysts and photocatalysts for the hydration of propene to 2-propanol. The characterization of the samples, particularly the electron paramagnetic resonance (EPR) spectroscopy results and the acidity properties, were useful to explain the key role played by the PW 12 in the composite materials in the thermal and photoassisted catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Gaigneaux et al have observed that the use of TiO2 as support, in comparison to the use of boron nitride with a more hydrophobic surface, could induce a better dispersion by virtue of its hydroxylated surface, but at the same time TiO2 could give rise to a decrease of the acidic strength of the HPA [19]. As far as the catalytic photo-assisted activity of the supported HPAs is concerned, it has been demonstrated that the use of semiconductor oxides as supports plays a beneficial role in the cluster photocatalytic activity due to the ability of the activated HPA * species to be reduced by the photogenerated electrons of the conduction band of the UVactivated semiconductor [5,20]. In order to study the local structural effects generated by the supports on the HPAs clusters, X-ray absorption spectroscopy (XAS) can be very useful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaigneaux et al have observed that the use of TiO2 as support, in comparison to the use of boron nitride with a more hydrophobic surface, could induce a better dispersion by virtue of its hydroxylated surface, but at the same time TiO2 could give rise to a decrease of the acidic strength of the HPA [19]. As far as the catalytic photo-assisted activity of the supported HPAs is concerned, it has been demonstrated that the use of semiconductor oxides as supports plays a beneficial role in the cluster photocatalytic activity due to the ability of the activated HPA * species to be reduced by the photogenerated electrons of the conduction band of the UVactivated semiconductor [5,20]. In order to study the local structural effects generated by the supports on the HPAs clusters, X-ray absorption spectroscopy (XAS) can be very useful.…”
Section: Introductionmentioning
confidence: 99%
“…19 As far as the catalytic photoassisted activity of the supported HPAs is concerned, it has been demonstrated that the use of semiconductor oxides as supports plays a beneficial role in the cluster photocatalytic activity due to the ability of the activated HPA* species to be reduced by the photogenerated electrons of the conduction band of the UV-activated semiconductor. 5,20 To study the local structural effects generated by the supports on the HPAs clusters, X-ray absorption spectroscopy (XAS) can be very useful. XAS is one of the most employed techniques in the heterogeneous catalysis and can be stated as an informative spectroscopy to study W species on several supports.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a photocatalyst as a support for HPAs further improved the activity of the composite, particularly under irradiation [23,24]. In the last case the increase of activity was correlated, thanks to the electron paramagnetic resonance (EPR) study, to the capability of the semiconductor to transfer photo-generated electrons to the activated HPA* species that consequently hinders the electron-hole pair recombination [25].…”
Section: Introductionmentioning
confidence: 99%